2022
DOI: 10.1186/s12957-022-02493-6
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of renal cell carcinoma as first and second primary cancers

Abstract: Objective Second primary renal cell carcinoma (2nd RCC) refers to renal cell carcinoma (RCC) diagnosed after another unrelated malignancy. This study aims to compare the clinical manifestation, pathology, treatment, and prognostic features of patients with 2nd RCC and first primary renal cell carcinoma (1st RCC). Materials and methods Data of the patients with localized RCC were retrospectively collected. They were classified as 2nd RCC or 1st RCC … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Other study conducted by Chen and colleagues found that 61.9% of patients with renal cell carcinoma diagnosed to have another primary tumour. According to this result, it is recommended to do full systematic examination in patients with renal cell carcinoma in order not to miss the diagnosis of other primary tumours 18 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other study conducted by Chen and colleagues found that 61.9% of patients with renal cell carcinoma diagnosed to have another primary tumour. According to this result, it is recommended to do full systematic examination in patients with renal cell carcinoma in order not to miss the diagnosis of other primary tumours 18 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, greater access to surveillance imagining leads to increase the rates of detection of incidental renal masses which could be diagnosed later as secondary renal cell carcinoma. It is worth to mention that patients diagnosed with secondary renal cell carcinoma are found to have less symptoms and fewer tumour sizes than those diagnosed as primary renal cell carcinoma 18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it has been found that NK cell activity is markedly reduced in hepatocellular carcinoma patients and associated with poor prognosis (15)(16)(17). Renal cell carcinoma (RCC) is one of the most common malignant tumours in the urinary system, and its poor prognosis may result from escape from NK cell cytotoxicity by kidney cancer cells (18,19). There have also been some studies investigating the correlation of NK cell receptors and RCC.…”
Section: In Renal Cancer Tissue Was Decreased Though Inhibitory Cytok...mentioning
confidence: 99%